Exploring the value of blood urea nitrogen-to-albumin ratio in patients with acute pancreatitis admitted to the intensive care unit: a retrospective cohort study - Wang, Jianjun; Li, Han; Yang, Pei; Chen, Xi; Chen, Sirui; Deng, Lan; Zeng, Xintao; Luo, Huiwen; Zhang, Dongqing; Cai, Xianfu; Luo, Hua; Wang, Decai (Frontiers in Nutrition, 2025)
BackgroundAlthough blood urea nitrogen and albumin alone are well-known clinical indicators, combining them as the blood urea nitrogen-to-albumin ratio (BAR) may provide additional prognostic information because they reflect the complex interplay between renal function, nutritional status, and systemic inflammation—all of which are key factors in the pathogenesis of acute pancreatitis (AP). Therefore, the objective of this study was to investigate the relationships between BAR and short- and long-term all-cause mortality (ACM) in patients with AP and to assess the prognostic significance of the BAR in AP.MethodsThis retrospective investigation utilized information extracted from the Medical Information Mart for Intensive Care-IV (MIMIC-IV, Version 2.2) database. BAR was calculated using the BUN/ALB ratio obtained from the first measurement within 24 h of admission. R software was used to identify the optimal threshold for the BAR. The Kaplan–Meier (K–M) analysis was performed to compare mortality between the two groups. Multivariate Cox proportional hazards regression models and restricted cubic splines (RCS) were used to evaluate the association between BAR and 14-day, 28-day, 90-day, and 1-year ACM. The receiver operating characteristic curves were used to investigate the predictive ability, sensitivity, specificity, and area under the curve (AUC) of the BAR for short- and long-term mortality in AP patients. Subgroup analysis was performed to illustrate the reliability of our findings.ResultsThis study comprised a total of 569 patients. The R software determined the optimal threshold for the BAR to be 16.92. The K–M analysis indicated a notable rise in ACM in patients with higher BAR (all log-rank p < 0.001). Cox proportional hazard regression models revealed independent associations between higher BAR and ACM before and after adjusting for confounding variables at days 14, 28, 90, and 1 year. The RCS analysis revealed J-shaped correlations between the BAR and short- and long-term ACM. The AUCs of the BAR for predicting ACM at days 14, 28, 90, and 1 year were 73.23, 76.14, 73.49, and 71.00%, respectively, which were superior to those of BUN, ALB, creatinine, Sequential Organ Failure Assessment, and Acute Physiology and Chronic Health Evaluation-II. Subgroup analyses revealed no significant interaction between BAR and the vast majority of subgroups.ConclusionThis study revealed, for the first time, the unique prognostic value of BAR in ICU-managed AP patients. Higher levels of BAR were associated with higher short- and long-term ACM in ICU-managed AP patients.